2011
DOI: 10.1093/pubmed/fdr028
|View full text |Cite
|
Sign up to set email alerts
|

Where do young adults want opportunistic chlamydia screening services to be located?

Abstract: Opportunistic chlamydia screening services should be located in traditional healthcare/medical settings, and screening should be offered by doctors and nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, when considered separately, the TCSB variables had been found to correlate with STI screening behaviors. Researchers have found that young women's affect can influence STI screening, including feelings of: (a) fear that their parents will find out that they have been screened, (b) fear, guilt, shame, and stigma about positive test results, (c) anxiety or uncertainty about their STI status, (d) worry about a recent sexual encounter, and (e) peace of mind in finding out that they do not have STIs (Balfe & Brugha, ; Balfe et al., ,b Blake et al., ; Brugha et al., ; Chacko et al., ; Friedman & Bloodgood, ; Tilson et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when considered separately, the TCSB variables had been found to correlate with STI screening behaviors. Researchers have found that young women's affect can influence STI screening, including feelings of: (a) fear that their parents will find out that they have been screened, (b) fear, guilt, shame, and stigma about positive test results, (c) anxiety or uncertainty about their STI status, (d) worry about a recent sexual encounter, and (e) peace of mind in finding out that they do not have STIs (Balfe & Brugha, ; Balfe et al., ,b Blake et al., ; Brugha et al., ; Chacko et al., ; Friedman & Bloodgood, ; Tilson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Utility beliefs, measured as women's perceptions about managing one's health or getting STI treatment if needed, have been reported by women to influence their screening (Blake et al., ; Brugha et al., ; Chacko et al., ). Norms reflecting screening have been studied as recommendations by health care providers and as desires to prevent spreading STIs to others (Brugha et al., ; Chacko et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,4] Screening for, or being diagnosed with an STD is often associated with embarrassment, stigma and anxiety. [5][6][7] Existing research shows that young adults feel exposed when getting tested for an STD, because they worry it will lead to a negative impact on their social status. [8,9] Other studies also point out, that young people choose, not to get tested due to the lack of knowledge about STDs and argue that young people do not perceive themselves at risk of contracting an STD.…”
Section: Introductionmentioning
confidence: 99%